Advances in Aerospace Guidance, Navigation and Control Selected Papers of the Third CEAS Specialist Conference on Guidance, Navigation and Control held in Toulouse - Bordeneuve-Guibé, Joël; Drouin, Antoine; Roos, Clément (Springer International Publishing : Imprint: Springer, 2015)
The two first CEAS (Council of European Aerospace Societies) Specialist Conferences on Guidance, Navigation and Control (CEAS EuroGNC) were held in Munich, Germany in 2011 and in Delft, The Netherlands in 2013. ONERA The French Aerospace Lab, ISAE (Institut Supérieur de l'Aéronautique et de l'Espace) and ENAC (Ecole Nationale de l'Aviation Civile) accepted the challenge of jointly organizing the 3rd edition. The conference aims at promoting new advances in aerospace GNC theory and technologies for enhancing safety, survivability, efficiency, performance, autonomy and intelligence of aerospace systems. It represents a unique forum for communication and information exchange between specialists in the fields of GNC systems design and operation, including air traffic management. This book contains the forty best papers and gives an interesting snapshot of the latest advances over the following topics: l  Control theory, analysis, and design l  Novel navigation, estimation, and tracking methods l  Aircraft, spacecraft, missile and UAV guidance, navigation, and control l  Flight testing and experimental results l  Intelligent control in aerospace applications l  Aerospace robotics and unmanned/autonomous systems l  Sensor systems for guidance, navigation and control l  Guidance, navigation, and control concepts in air traffic control systems For the 3rd CEAS Specialist Conference on Guidance, Navigation and Control the International Program Committee conducted a formal review process. Each paper was reviewed in compliance with standard journal practice by at least two independent and anonymous reviewers. The papers published in this book were selected from the conference proceedings based on the results and recommendations from the reviewers.